Quality Analysis of Low-Code No-Code Application Development Using ISO/IEC 25010 Standard: A Systematic Literature Review - Hanggoro, Dimas Banu Dwi; Kurniawati, Laela; Rianto, Yan (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
The acceleration of digital transformation has increased the demand for fast and efficient software development. This condition has led to the emergence of Low-Code/No-Code (LC/NC) approaches, which allow users with limited technical expertise to build applications through visual interfaces and pre-built components. This study aims to analyze the quality of Low-Code No-Code (LCNC) application development based on the ISO/IEC 25010 standard through a Systematic Literature Review (SLR) method, supported by bibliometric visualization using VOSviewer software. The reviewed articles were published between 2020 and 2024. The visualization results indicate that keywords such as context, development, and system are the primary focus in the study of LCNC application quality. Furthermore, the findings of Meira et al. (2020) demonstrate that the Analytical Hierarchy Process (AHP) method, when combined with the ISO/IEC 25010 standard, is effective in evaluating and comparing software system quality within an industrial context. This study concludes that a standards-based evaluation approach, complemented by bibliometric visualization, can provide valuable insights for decision-making processes related to the development and implementation of LCNC applications.